Does the transfer of a poor quality embryo together with a good quality embryo affect the In Vitro Fertilization (IVF) outcome?. Issue 1 (December 2017) - Wintner, Eliana; Hershko-Klement, Anat; Tzadikevitch, Keren; Ghetler, Yehudith; Gonen, Ofer; Wintner, Oren; Shulman, Adrian; Wiser, Amir
Abstract Background IVF cycles which result in only one good quality embryo, and a second poor quality embryo present a dilemma when the decision involves transferring two embryos. The aim of this study was to evaluate whether a poor quality embryo has a negative effect on a good quality embryo when transferred along with a good quality embryo. Methods We retrospectively evaluated in vitro fertilization (IVF) cycles involving single embryo transfers (SET) and double embryo transfers (DET). Embryo quality was divided into poor "P" and good "G" quality. The main outcome measures were: live birth, implantation rate, miscarriage rate, clinical pregnancy rate and multiple pregnancy ratio. Results Six hundred three women were included. The study group consisted of 180 (29.9%) patients who had a double embryo transfer (DET) with one poor quality embryo and one good quality embryo (P + G). Control 1 group included 303 (50.2%) patients who had DET with two good quality embryos (G + G), and control 2 group consisted of 120 (19.9%) patients who had a single embryo transfer (SET) with one good quality embryo (G). Live birth rates were not significantly different when compared between study groups: 30.8% in the SET group (G), 27.2% in the (G + P) group and 33.7% in the (G + G) group. The SET group had the highest implantation rate (33.9%) compared to the DET groups (21.8% (G + P), 25.4% (G + G)) (P =0.022). The clinical pregnancy rate was 33.3% in the SET group (G), 33.3% in the (G + P) group, and 39.3% in the (G + G) group (P =0.39). The miscarriage rate was comparable in all groups. Conclusion A poor quality embryo does not negatively affect a good quality embryo, when transferred together in a double embryo transfer.